Coalbed methane accumulation and dissipation patterns: A Case study of the Junggar Basin, NW China. (July 2018) - Li, Xin; Fu, Xuehai; Yang, Xuesong; Ge, Yanyan; Quan, Fangkai
Graphical abstract: Highlights: CBM accumulation and dissipation patterns of the Junggar Basin were proposed based on five aspects of geological factors. CBM origin was found to be different under different geological conditions in the Junggar Basin. Two types of CBM migration were found in different coal profiles of the Junggar Basin. Abstract: The Junggar Basin is a potential replacement area of coalbed methane (CBM) development in China. To improve the efficiency of CBM exploration, we investigated CBM accumulation and dissipation patterns of coal profiles located in the northwestern, southern, eastern, and central Junggar Basin based on the following criteria: burial depth, hydrogeological zone, CBM origin, CBM phase, and CBM migration type. We identified four types of CBM accumulation patterns: (1) a self-sourcing CBM pattern containing adsorbed gas of biogenic origin from shallow-depth coal within a weak runoff zone; (2) an endogenic migration pattern containing adsorbed gas of thermogenic origin from the medium and deep coals within a stagnant zone; (3) an exogenic migration pattern containing adsorbed gas of thermogenic origin from deep coal within a stagnant zone; and (4) an exogenic migration pattern containing adsorbed and free gas of thermogenic origin from ultra-deep coal within a stagnant zone. We also identified two types of CBM dissipation patterns: (1) shallow-depth coal within a runoff zone with mixed origin CBM; and (2) shallow and medium-deep coal seams with mixed origin CBM. CBM migration in low-rank coals was more substantial than that adsorbed in high-rank coal. CBM in shallow coal could easily escape, in the absence of closed structures or hydrogeological seals. CBM reservoirs occurred in deep coal where oversaturated gas may accumulate. Future exploration should focus on gas-water sealing structures in shallow coalbeds. CBM that occurred in adsorbed and free phases and other unconventional natural gas dominated by free gas in the coal stratum should be co-explored and co-developed.